Studies on transport of carbonate ions through a supported liquid membrane - Gaikwad, Abaji G. (Chemical and Biochemical Engineering Quarterly, 2009)
The transport of carbonate ions through a supported liquid membrane in the presence and absence of carriers has been explored. The liquid membrane used was the combined liquid cation and anion exchangers in toluene immobilized in the porous polypropylene support. The permeability coefficient (P) of carbonate ions transport from the source to receiving through membrane phase has been estimated. The different experimental variables such as the concentration of carbonate ions in source phase, the concentration of Aliquat-336 (tricapryl(methyl)ammonium carbonate) and PC-88A (2-ethyl-hexyl phosphonic acid mono-2-ethylhexyl ester) in membrane phase, alkali metal hydroxide concentration in receiving phase, and the stirring speed of the Source phase and receiving phase have been explored. The stability of liquid membrane phase during the transport of carbonate ions from source phase to receiving phase was tested for 50 h. The enrichment factor for carbonate ion transport from the source to receiving phase was found to be higher at lower concentrations of carbonate ions in comparison with that of at higher concentrations. A model has been developed for the effective transport of carbonate ions through the cross section area of liquid membrane phase from source to receiving phase.
Keywords: alkali metal hydroxide; carbonate ions; liquid anion and cation exchangers; permeability coefficient; supported liquid membrane